Examine The Concept of Forgiveness in Juvenile Cases as Per Article 70 of The Judicial System Act Regarding Children's Criminal Responsibility - Mashendra (AIQU: Journal Multidiscipliner of Science, 2024)
This paper aims to explore the meaning of forgiveness of judges set out in Article 70 Law No. 11 of 2012 on juvenile criminal justice system (SPPA). When examined further, the explanation of Article 70 of the law only contains the word”self-explanatory". This normative research uses legislation and conceptual approach. The results showed that the meaning of Article 70 of the SPPA law is punishment to the child can only be applied as a last resort by basing value of humanity and justice for children by basing on the philosophical basis of value- values of Pancasila and the Constitution of 1945, and rests on the implementation of the principles child protection